Identification of Environmental Chemicals Associated with the Development of Toxicant-associated Fatty Liver Disease in Rodents. (June 2015) - Al-Eryani, Laila; Wahlang, Banrida; Falkner, K. C.; Guardiola, J. J.; Clair, H. B.; Prough, R. A.; Cave, Matt
Background: Toxicant-associated fatty liver disease (TAFLD) is a recently identified form of nonalcoholic fatty liver disease (NAFLD) associated with exposure to industrial chemicals and environmental pollutants. Numerous studies have been conducted to test the association between industrial chemicals/environmental pollutants and fatty liver disease both in vivo and in vitro . Objectives: The objective of the article is to report a list of chemicals associated with TAFLD. Methods: Two federal databases of rodent toxicology studies—Toxicological Reference Database (ToxRefDB; Environmental Protection Agency) and Chemical Effects in Biological Systems (CEBS, National Toxicology Program)—were searched for liver end points. Combined, these 2 databases archive nearly 2, 000 rodent studies. Toxicant-associated steatohepatitis (TASH) descriptors including fatty change, fatty necrosis, Oil red O-positive staining, steatosis, and lipid deposition were queried. Results: Using these search terms, 123 chemicals associated with fatty liver were identified. Pesticides and solvents were the most frequently identified chemicals, while polychlorinated biphenyls (PCBs)/dioxins were the most potent. About 44% of identified compounds were pesticides or their intermediates, and >10% of pesticide registration studies in ToxRefDB were associated with fatty liver. Fungicides and herbicides were more frequently associated with fatty liver than insecticides. Conclusion: More research on pesticides, solvents, metals, and PCBs/dioxins in NAFLD/TAFLD is warranted due to their association with liver damage.